Peculiarities of the Formation of Educational Trajectories of Russian Students: Assessment and Opportunities - I. A. Aleshkovski; A. T. Gasparishvili; O. V. Krukhmaleva; N. P. Narbut; N. Ye. Savina (Moscow Polytechnic University, 2023)
New geopolitical challenges that necessitate the formation of a nationally oriented education system require a multidimensional analysis, socio-cultural understanding and the search for new formats for the organization of higher education in Russia. In the conditions of the post-Bologna reality, Russia needs to create its own model of higher education, which will be able to provide the economy with highly qualified personnel, which will coopt all the best from the classical Soviet system of education and will be able to build on the national traditions, interests of students, their parents, teachers and employers. In this regard, it is relevant to analyze and evaluate the requests of nowadays students for these changes and the nature of those changes.The article is based on the materials of the authors' sociological research (N=123977 people), conducted in 2022.The problematic area of the research supposed that the revision of the existing predominantly two-level (bachelor and master) structure of higher education requires a transition to the optimal and traditional for Russia model of the specialist program with the introduction of more flexible forms of work, the possibility of changing the educational trajectory in the learning process, the search for new ways of academic mobility and universities cooperation.The research data are compared with the data of similar works of Russian and foreign analysts. An analysis of the opinion of Russian students showed that in the process of learning and gradually entering a specialty, some students need certain changes in the chosen training program made upon admission. The possibility or impossibility of implementing these changes determines their motivation for learning, academic achievements, further educational and professional trajectories, and satisfaction with education in general. Based on the analysis done and the results obtained, the authors propose practical steps to form a new structure of higher education based on the specialist program. They suggest recommendations on the necessary changes in the legislative, organizational, educational and methodological nature related to this process.